EFFECT OF SEED PRIMING AND PLANTING DATES ON SOME GROWTH CHARACTERISTICS OF TWO CULTIVARS OF SOYBEAN - S , Mohsen, M.; H, Saudi, A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
A field experiment was conducted to investigate the effect of seed priming and planting dates on the growth of two soybean cultivars. This study was conducted during the summer seasons 2022 and 2023 at the fields of the Agricultural Engineering Sciences - University of Baghdad. A Randomized Complete Block Design (RCBD) split-split plot arrangement was employed, with three replicates and three factors. The main factor included planting dates (1/6, 15/6, and 1/7), the second factor included two soybean cultivars (Lee 74 and Shaimaa), and the third factor included seed priming treatments (Gibberellic acid, KCl, and seaweed extract as well as two control treatments (soaking with distilled water and dry seeds). The results showed the superiority of the 15th June planting date, with the highest average plant height and crop growth rate. The Shaimaa cultivar exhibited the highest average in leaf area and crop growth rate, while also outperforming in plant height. The seed priming treatment with seaweed extract excelled in leaf area and crop growth rate, while the KCL treatment excelled in plant height. Overall, 15th June planting date and the Shaimaa cultivar showed superiority, along with the seaweed extract seed priming treatment.